On the effects of intergovernmental grants: A survey - Manuel E. Lago; Santiago Lago Pe\~nas; Jorge Martinez-Vazquez (University College Dublin, UCD School of Economics, 2022)
This paper offers a comprehensive and updated review of the effects of intergovernmental grants. We focus on the main findings in the existing literature on the effects of intergovernmental grants on tax policy and choices, expenditure decisions, fiscal stability and behavioral choices, and political economy. The intricate nature of the subject, innately, does not allow for an all-inclusive survey, but we aim to provide a thorough examination and update of the most salient effects of intergovernmental grants, while indicating areas for further research.
Keywords: H71; H72; H77; 330; Intergovernmental transfers; effects; fiscal decentralization